2015
DOI: 10.5935/0004-2749.20150014
|View full text |Cite
|
Sign up to set email alerts
|

Case report: pneumatic retinopexy for the treatment of progressive retinal detachment in senile retinoschisis

Abstract: Retinoschisis is an abnormal separation of the retinal layers and is asymptomatic in most cases. Enlargement of the area of retinoschisis and retinal tear and detachment are possible complications of the disease, and the treatment of retinoschisis is controversial. In this case report, we present a case of retinal detachment associated with senile retinoschisis in which pneumatic retinopexy was chosen as the treatment of choice and was performed successfully in one of the eyes. After a literature review on ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Our anatomic success rate with SB alone or in combination with VIT, while not statistically superior to VIT alone, seems to support this practice pattern. Despite several case reports that demonstrated the success of pneumatic retinopexy in treating a retinoschisis-related detachment, [18][19][20] we have hesitated to offer this procedure to patients with a retinoschisis-related detachment until a larger study is published that demonstrates efficacy equivalent to SB or VIT.…”
Section: Discussionmentioning
confidence: 99%
“…Our anatomic success rate with SB alone or in combination with VIT, while not statistically superior to VIT alone, seems to support this practice pattern. Despite several case reports that demonstrated the success of pneumatic retinopexy in treating a retinoschisis-related detachment, [18][19][20] we have hesitated to offer this procedure to patients with a retinoschisis-related detachment until a larger study is published that demonstrates efficacy equivalent to SB or VIT.…”
Section: Discussionmentioning
confidence: 99%
“…Superior temporal retinal tear had operculated and traction was released [17]. Suzuki et al [18] reported a case of successful pneumatic retinopexy for retinal detachment associated with a progressive superior temporal retinoschisis.…”
mentioning
confidence: 99%